BirdLasser: The influence of a mobile app on a citizen science project. Issue 2 (2nd April 2020) - Lee, Alan Tristram Kenneth; Nel, Henk
Abstract : In recent decades, people across the world have adopted 'smart-phones' and their technology. Software applications on these devices have become diverse in their functionality and easy to use. Citizen science projects that try to mobilise data collection from people from diverse backgrounds are ideally placed to benefit from the acceptance of easy-to-use technology. This article describes the development of the mobile BirdLasser app and its integrated gamification network, with emphasis on how its unique features contributed to increased participation and submission of data to the current Southern African Bird Atlas Project (SABAP2) and associated BirdMap projects across Africa. The app has experienced a high adoption rate by contributors to SABAP2 (atlassers), birdwatchers and conservationists, contributing to causes, creating life lists and taking part in events. The app has been associated with the recruitment of new participants, but this has also seen a change in atlassing patterns, suggesting caution when using traditional measures of abundance comparisons, especially reporting rate, before and after the adoption of BirdLasser as the data submission pathway. We show that a well-designed mobile app that facilitates the flow of information from observers to databases is essential for maintaining long-term citizen science based, monitoring projects, especially if the platform is fun, well-supported, and free to use; but the introduction of an app may also introduce subtle changes to the data itself and so data submission pathways to citizen science projects is a field that requires additional research.